Ferroptosis: A critical link to treatment resistance in esophageal carcinoma - Ming-Xin Tang; Jin-Feng Chen; Fa-Zhi Zhao; Jun Peng (iScience)
Summary: Ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxide accumulation, induces lethal oxidative damage and disrupts cell membrane integrity. Its role in malignant tumors, such as esophageal carcinoma (EC), is increasingly recognized, offering a promising therapeutic avenue to overcome treatment resistance. Emerging evidence highlights the involvement of genes, proteins, the metabolism of metal ions, and tumor microenvironmental factors in modulating ferroptosis-associated resistance mechanisms in EC. This review systematically outlines current insights into ferroptosis in EC resistance and explores novel therapeutic strategies, including ferroptosis-targeted agents, nanotechnology, natural compounds, and multimodal approaches. Nevertheless, overcoming EC resistance remains a significant clinical challenge, warranting further investigation.